Introduction to nanotechnology in eco-efficient construction - Pacheco-Torgal, F. (2013)
This chapter provides a brief overview of some important aspects of nanotechnology starting with its earlier steps and how countries are trying to establish an advantageous position in this field. China deserves a special mention because it is already the second largest producer of nanotechnology papers after the United States. The need for nanotechnology in the construction sector is emphasized. An outline of the book is given.